2021
DOI: 10.1038/s41525-021-00209-5
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous preterm birth: the underpinnings in the maternal and fetal genomes

Abstract: Preterm birth (PTB) is a major cause of neonatal mortality and health complications in infants. Elucidation of its genetic underpinnings can lead to improved understanding of the biological mechanisms and boost the development of methods to predict PTB. Although recent genome-based studies of both mother and fetus have identified several genetic loci which might be implicated in PTB, these results suffer from a lack of consistency across multiple studies and populations. Moreover, results of functional validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…We defined preterm birth and very preterm birth as a live birth before 37 and 32 completed weeks of gestation, respectively. Preterm birth subtype was considered spontaneous if it occurred after spontaneous onset of labour or preterm premature rupture of membranes 30. Small for gestational age at birth was defined as a singleton live born infant below the 10th centile of the sex specific birth weight for gestational age distribution, based on a Canadian reference standard 31.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We defined preterm birth and very preterm birth as a live birth before 37 and 32 completed weeks of gestation, respectively. Preterm birth subtype was considered spontaneous if it occurred after spontaneous onset of labour or preterm premature rupture of membranes 30. Small for gestational age at birth was defined as a singleton live born infant below the 10th centile of the sex specific birth weight for gestational age distribution, based on a Canadian reference standard 31.…”
Section: Methodsmentioning
confidence: 99%
“…Preterm birth subtype was considered spontaneous if it occurred after spontaneous onset of labour or preterm premature rupture of membranes. 30 Small for gestational age at birth was defined as a singleton live born infant below the 10th centile of the sex specific birth weight for gestational age distribution, based on a Canadian reference standard. 31 Stillbirth was defined as an antepartum or intrapartum on 21 August 2022 by guest.…”
Section: Outcome Variablesmentioning
confidence: 99%
“…Examining only the direct associations of traits without accounting for environmental exposures may result in missing relevant genes which influence sPTB. 114 To overcome this, a genome-wide gene × environment interaction analysis to explore the "missing heritability" of preterm birth in 1733 African-American women (n = 698 preterm birth and 1035 of term birth) showed that maternal COL24A1 variants have significant genome-wide interaction with maternal pre-pregnancy overweight/obesity on preterm birth risk. The interaction effect size and direction were comparable across all subtypes of preterm birth, including spontaneous, medically indicated, early preterm birth (< 32 weeks), late preterm birth (32-37 weeks), and preterm birth with chorioamnionitis.…”
Section: Environmental Exposure and Preterm Birthmentioning
confidence: 99%
“…However, most genetic studies on sPTB have failed to consider the genetic and environmental interactions which could be one of the reasons for the lack of replication in genetic studies. Examining only the direct associations of traits without accounting for environmental exposures may result in missing relevant genes which influence sPTB 114 . To overcome this, a genome‐wide gene × environment interaction analysis to explore the “missing heritability” of preterm birth in 1733 African‐American women ( n = 698 preterm birth and 1035 of term birth) showed that maternal COL24A1 variants have significant genome‐wide interaction with maternal pre‐pregnancy overweight/obesity on preterm birth risk.…”
Section: Environmental Exposure and Preterm Birthmentioning
confidence: 99%
“…The prevalence of preterm birth in Denmark was specified to be 5% according to a systematic analysis (Blencowe et al, 2012). Genes TEKT3 and IGF1R were reported to be significantly associated with preterm birth and birth weight in G. Zhang et al (2017) and Bhattacharjee and Maitra (2021), respectively, and some SNPs in gene TEKT3 and IGF1R were identified with a significant association with preterm birth. Our aim was to assess POEs of those candidate SNPs genotyped in this data set.…”
Section: Real Data Analysismentioning
confidence: 99%